Effects of an Enzymatically Hydrolyzed Yeast and Yeast Culture Combined with Flavomycin and Monensin on Finishing Broiler Chickens - Gomez, Sergio; Angeles, Maria de Lourdes (International Journal of Poultry Science, 2011)
An experiment was carried out to evaluate the relationship of an Enzymatically Hydrolyzed Yeast (EHY) and yeast culture combined with flavomycin and monensin (F + M) under two levels of Digestible Lysine (DLYS) on the growth performance, carcass measurements, nutrient retention and AMEn in broilers. One hundred and thirty two 35 d old Ross B308 male broilers individually housed in holding cages were used. Broilers were assigned to a factorial arrangement of 2 levels of EHY (0 and 1 kg/ton of feed) x 2 levels of F + M (0.0 and 0.05,0.50 kg/ton) x 2 DLYS levels (0.85 and 0.95%). The experiment lasted 2 wks. Results were subjected to analysis of varianza. EHY-fed broilers showed a trend for greater (p<0.10) feed intake, had improved (p<0.05) weight gain, feed conversion ratio and had greater (p<0.01) weight and yield of the carcass, breast and legs. Broilers fed EHY and 0.95% DLYS had higher nitrogen intake and retention and lower AMEn than those with 0.85% DLYS (EHY and DLYS interaction, p<0.05). EHY-fed broilers also had greater dry matter and ashes intake (p<0.01) and retention (p<0.05). The addition of F+M to the diet improved the weight gain (p<0.05), feed conversion ratio (p<0.01), nitrogen retention and AMEn (p<0.05). Broilers fed the 0.95% DLYS diet had greater feed conversion (p<0.05). The addition of EHY and F+M improved the production and nutrient use in broilers but their effects were independent. The EHY and DLYS showed an additive or synergistic relationship on the nitrogen intake and retention and AMEn.